Rhodium(III)-Catalyzed C–H Activation-Based First Total Synthesis of 6-O-Methyl Anciscochine, an Alkaloid Isolated from Ancistrocladus tectorius - Vargas, Didier F.; Romero, Brenda S.; Larghi, Enrique L.; Kaufman, Teodoro S. (Synthesis, 2020)
The concise and efficient first total synthesis of 6-O-methyl anciscochine, employing a tandem C–C/C–N formation approach via a rhodium-catalyzed C–H activation/alkenylation/annulation strategy, is reported. This heterocycle was isolated from the liana Ancystrocladus tectorius and features a unique 3-hydroxymethylisoquinoline core that is found in a few other natural products and in some bioactive synthetic compounds. The synthesis, which was executed in four high-yielding steps and a global yield of 43%, involved the oximation of commercial 2,4-dimethoxyacetophenone under CeCl3·7H2O-promotion, followed by pivaloylation of the oxime. A one-pot pivaloxime-directed alkenylation/annulation stage with methyl acrylate, furthered by a NaBH4/ CaCl2-mediated reduction of the resulting isoquinoline 3-carboxylate ester completed the sequence.
Keywords: C–H activation; natural product; rhodium catalysis; 6-O-methyl anciscochine; Ancystrocladus tectorius; one-pot alkenylation/ annulation